Networks : (World Scientific, 2002)
Proceedings of the Joint Intl Conference on Wireless LANs and Home Networks and Networking, held August 26-29, 2002. Covers a wide variety of technical sessions covering all aspects of networking technology. For graduate students, researchers and academics in networking and electrical and electronic engineering.